2006
DOI: 10.1016/j.seizure.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam in patients with generalised epilepsy and myoclonic seizures: An open label study

Abstract: Our results confirm that LEV as de novo (monotherapy) and add-on therapy at doses between 2000 and 3000 mg/day effectively reduces myoclonic seizure frequency in patients with generalised epilepsy. LEV was also well-tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 10 publications
3
50
0
Order By: Relevance
“…23,24 Our study evaluated both the efficacy and the safety of LEV in the treatment of JME and our results reinforce the concept that LEV works very well in the treatment of JME. A very recent study 15 showed a good response in 35 patients with different types of epilepsy (but all characterized by prominent myoclonic seizures). In fact, myoclonus responded dramatically to LEV and a total of 29 patients obtained seizure reduction.…”
Section: Discussionmentioning
confidence: 98%
“…23,24 Our study evaluated both the efficacy and the safety of LEV in the treatment of JME and our results reinforce the concept that LEV works very well in the treatment of JME. A very recent study 15 showed a good response in 35 patients with different types of epilepsy (but all characterized by prominent myoclonic seizures). In fact, myoclonus responded dramatically to LEV and a total of 29 patients obtained seizure reduction.…”
Section: Discussionmentioning
confidence: 98%
“…Open-label trials in children have demonstrated good efficacy and tolerability in refractory mixed seizure disorders (19,20) Efficacy in primary generalized epilepsy, such as juvenile myoclonic epilepsy, has also been established; however, rarely, myoclonic seizure may be worsened by this drug (21,22). Levetiracetam is excreted primarily by the kidneys with minimal hepatic metabolism.…”
Section: Levetiracetammentioning
confidence: 99%
“…women, and it is characterized by frequent bilateral myoclonic jerks of the arms associated at times with generalized tonic-clonic or absence seizures with a good response to antiepileptic drugs [3][4][5]. Habitually, menstrual period and sleep deprivation can trigger seizures.…”
mentioning
confidence: 99%
“…Habitually, menstrual period and sleep deprivation can trigger seizures. Seizures are very well controlled by appropriate therapy in up to 90% of subjects [3,4]. Generalized 3-6 Hz polyspike-wave (PSW) discharges are the cornerstone in the diagnosis and treatment of JME [3][4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation